Analysis of the calculation of support nodes bolted connections of cantilevered steel-reinforced concrete posts (Academic journal Industrial Machine Building Civil Engineering, 2023)
In order to reduce steel consumption in the installation of support nodes of cantilevered pipe reinforced concrete advertising structures, the optimal ratio of the base plate size and the diameter of the support node anchor bolts of an existing advertising structure was calculated. The analysis of the calculations revealed the total cost dependence of the support node and anchor bolts on the overall node dimensions and the anchor bolts diameter. With an increase in the size of the support node, the cost of the support node metal increases much faster than the cost of the anchor bolts decreases. For more efficient use of materials, it is necessary to reduce the size of the node and increase the diameter of the anchor bolts accordingly. As a result of the research and calculations, the most efficient support node was determined. The savings in the total cost of such a node is 8.9% compared to the existing support node of the studied advertising structure
Keywords: wind load; support node; bolted connection; cantilever construction